Impact of the Covid-19 Outbreaks on Digital Payments-A Study in Bengaluru City - Nandisha, H. D.; Kavya, M. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
In the current situation, digital payments play a key role. The epidemic could affect the surrounding India. They are the most dangerous situations facing the world as a whole. Digital payments are guaranteed to be safe, secure and easy. The digital payment market would make up 71.7% of all transactions, and is helpful to customers. Payment systems have shown that these are reliable and durable, and they continue to show high confidence in the general public. However, the closure of the business and the closure of the results have resulted in lower transaction rates as a whole. In this paper we describe the various digital payment methods used in the event of a pandemic.